2021
DOI: 10.3390/medicina57010058
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Strategies for the Treatment of Chronic Hyperuricemia: An Evidence-Based Update

Abstract: This article aims to critically review the evidence on the available therapeutic strategies for the treatment of hyperuricemia. For this reason, several papers were reviewed. Xanthine oxidase inhibitors are the safest and most effective uric acid lowering drugs for the management of chronic hyperuricemia, while the efficacy of uricosuric agents is strongly modulated by pharmacogenetics. Emergent drugs (lesinurad, peglotidase) were found to be more effective for the acute management of refractory hyperuricemia,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 112 publications
1
61
0
3
Order By: Relevance
“…There are two main classes of hypouricemic agents: UA production inhibitors and UA excretion promoters [101,102]. So far, there have been only a few studies that have analyzed the effects of UA-lowering drugs in patients with hypertension [44][45][46][48][49][50][51][52][53][54][55][56][57][58][59]103] (Table 2).…”
Section: Ua Lowering-therapies Effects On Blood Pressurementioning
confidence: 99%
See 2 more Smart Citations
“…There are two main classes of hypouricemic agents: UA production inhibitors and UA excretion promoters [101,102]. So far, there have been only a few studies that have analyzed the effects of UA-lowering drugs in patients with hypertension [44][45][46][48][49][50][51][52][53][54][55][56][57][58][59]103] (Table 2).…”
Section: Ua Lowering-therapies Effects On Blood Pressurementioning
confidence: 99%
“…A recent systematic review of clinical practice guidelines and consensus statements on the treatment of hyperuricemia and gout recommended long-term treatment of patients with gout or with comorbities and SUA > 6.0 mg/dL (or 360 µmol/L) [102]. Even if treatment of asymptomatic patients without comorbities is still not recommended, large population studies such as the multicenter Uric Acid Right for Heart Health (UR-RAH) Study showed that the optimal SUA cut-off for reducing CV mortality was under 5.6 mg/dL [111][112][113].…”
Section: How To Choose the Right Hypouricemic Agentmentioning
confidence: 99%
See 1 more Smart Citation
“…Uricosuric drugs lower serum uric acid levels by blocking urate reabsorption transporters expressed by the renal tubular epithelial cells, including urate transporter 1 (URAT1) and glucose transporter 9 (GLUT9) [16,17]. However, commonly used uricosuric agents such as probenecid, benzbromarone, and febuxostat have also been known to interact with urate secretion transporters ABCG2, OAT1, and OAT3 [18,19]. The ability of benzbromarone and febuxostat, among other urate-lowering drugs, to inhibit urate secretion activity of ABCG2 has been demonstrated [20].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the role of ABCG2 in both renal and intestinal urate excretion, this could have a somewhat canceling effect on the hypouricemic activity of these drugs [16,20,21]. Furthermore, potent inhibitors of OAT seem to reduce the renal clearance of organic acids e.g., salicylates and methotrexate, resulting in drug-drug interactions [18,22,23]. Given the above, and the finding that URAT1 is the primary protein involved in the reabsorption of urate [23], the attention of new uricosuric agents is focused on selective inhibition of URAT1 to maximize efficacy and minimize unfavorable effects.…”
Section: Discussionmentioning
confidence: 99%